Manfaat Blockchain pada Sistem Registrasi Tanah: Systematic Literature Review - Suratmanto, Bekti; Emanuel, Andi Wahyu Raharjo (Jurnal Informatika: Jurnal Pengembangan IT, 2025)
The robust economic growth in Indonesia in the second quarter of 2023 indicates a projected population increase, leading to higher population density and driving the conversion of agricultural land. Land ownership has become a valuable source of capital, triggering intense competition. Land properties have emerged as valuable assets, emphasizing the importance of land registration as a process for recording ownership rights. The current centralized and manual land registration system faces challenges such as record duplications, unauthorized document reforms, and excessive departmental involvement. These weaknesses can result in pending cases, slow verification processes, and document manipulation.Digital transformation with blockchain technology is proposed as a solution for transparent, efficient, and legally certain land administration. This technology offers decentralized storage, resilience to changes, and peer-to-peer verification in transaction recording. While some countries have successfully implemented blockchain, others have faced failures due to environmental factors, state intervention, socio-political readiness, and institutional factors. In Indonesia, land conflicts have escalated, recording 562 cases from 1988 to July 2023. The lack of capacity and competence in local government human resources, coupled with suboptimal administration, complicates handling and hampers regional revenue. This research proposes a land registration framework with the implementation of blockchain as a solution to land administration issues in Indonesia.